ADMINISTRASI PENDIDIKAN BERMUTU BERBASIS GOOD TEACHER GOVERNANCE - Jonson Rajagukguk; Artha Lumbantobing (Jurnal Ilmu Sosial Dan Politik, 2021)
The future of education in our country is very dependent on the extent to which the quality and quality of teachers in this country. The quality of good teachers will encourage a very significant improvement in the quality of education. For this reason, careful planning is needed, evaluative actions that are routinely carried out so that we can see and analyze how ways and methods in supporting the quality of education depart from the quality of the teachers themselves. Currently, the paradigm of education governance is very dependent on the principles of transparency, accountability, good vision and mission. all of this can be done with a note that there is quality education administration. Quality education administration. One of the variables to be developed is a good teacher governance model called the concept of good teacher governance. How the role and function of the concept of good teacher management as an effort to create the concept of quality education administration in this country will be the main focus and study in this descriptive writing and review.